Remote monitoring of cancer patients during the Covid-19 pandemic - an interview study of nurses' and physicians' experiences - Vigdis Abrahamsen Grøndahl; Ann Karin Helgesen; Elisabet Holm; Jannik Magnussen; Ann-Chatrin Leonardsen (BMC, 2022)
Abstract Background Due to the Covid-19 pandemic, remote monitoring of patients outside hospitals rapidly increased. Previous studies show that healthcare professionals' competence in digitalization needs to be improved. Little is known about how Covid-19 has affected the use of remote monitoring of cancer patients. The purpose of the study was therefore to explore healthcare personnels' experiences with remote monitoring of cancer patients during the Covid-19 pandemic.  Methods The study had an explorative and descriptive design using semi-structured individual interviews for data collection. Data was analyzed by content analysis. Results A total of ten healthcare personnel working in the cancer department and out-patient cancer clinic in the hospital participated; four physicians and six registered nurses. Two categories and four subcategories were identified: 1) «Maintaining personalized healthcare services» comprising the subcategories a) «Adjusting services to patients' health condition» and b) «Ensuring continuity»; and 2) «A supplement, but not a replacement» comprising the subcategories a) «Impact on interpersonal relations» and b) «The importance of clinical assessment». Conclusions This study indicates that remote monitoring through telephone was preferred by both healthcare personnel and patients. The nurses and physicians experienced a more frequent contact with their patients, but emphasized the importance of physical meetings for building relationship, and for thorough clinical examination. Our findings indicate a need to facilitate a work environment where healthcare personnel can be fast learners in using digital tools to provide best possible healthcare quality. Moreover, it is imperative to develop a workplace suitable for the use of digital technology for remote monitoring, and to provide digital tools that is easy to use for both healthcare personnel and patients.